2007
DOI: 10.1634/theoncologist.12-5-524
|View full text |Cite
|
Sign up to set email alerts
|

Anal Cancer: An Overview

Abstract: LEARNING OBJECTIVESAfter completing this course, the reader will be able to:1. Discuss the epidemiology of and the risk factors for anal cancer.2. Outline standard treatment for anal cancer and describe its complications.3. Understand the issues related to treating HIV-positive patients with anal cancer.Access and take the CME test online and receive 1 AMA PRA Category 1 Credit ™ at CME.TheOncologist.com CME CME ABSTRACTAnal cancer is a rare tumor with an incidence that has been rising over the last 25 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(106 citation statements)
references
References 47 publications
1
94
0
11
Order By: Relevance
“…11 Anal carcinoma and AIN have both been linked to HPV infection, 1,2,12,13 of which over 100 genotypes have been identified. At least 40 subtypes are known to infect the anogenital mucosa with variable neoplastic risk.…”
Section: Discussionmentioning
confidence: 99%
“…11 Anal carcinoma and AIN have both been linked to HPV infection, 1,2,12,13 of which over 100 genotypes have been identified. At least 40 subtypes are known to infect the anogenital mucosa with variable neoplastic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma (SCC) represents the majority of all anal carcinomas [2,3]. Several risk factors have been associated with the development of anal carcinomas such as lifetime number of sexual partners, female gender, human papillomavirus (HPV) infection, human immunodeficiency virus (HIV) infection and men who have sex with men (MSM) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Of these potential endpoints, Prorok concluded that "there is only one outcome variable known to be valid: the cancer mortality rate", defined as "the number of cancer deaths per unit of time, per unit of population at risk." [10] The pretreatment prognosis for IAC is determined, in part, by TNM stage, location, cell differentiation, and comorbid conditions including HIV related immunosuppression [48][49][50][51]. Practice guidelines of the National Comprehensive Cancer Network [2] recommend initial local excision for stage T1,N0 (≤ 2 cm diameter, no regional lymph node metastases) anal margin carcinomas and chemoradiation for T1-2, N0 disease for anal canal carcinomas or anal margin carcinomas with positive margins at resection.…”
Section: Direct and Indirect Measures Of Screening Program Successmentioning
confidence: 99%